Incorporation of Dental Health Screening in Paediatric Office Practice - Dagli, Pallavi; Singh, Jyotsna; Sheth, Jay; Kakkad, Khyati (Journal of Nepal Paediatric Society, 2018)
Introduction: Dental health problems in children are often overlooked. Poor oral health negatively affects growth, learning, communication, self-esteem and rarely can also lead to serious fatal infection. Paediatrician can play key role in screening dental health problems. The objectives of this study were to screen children for dental caries in paediatric office and correlate with socio-demographic, dietary and oral hygiene risk factors. Material and Methods: After basic oral health training, paediatrician assessed oral health risk factors with pre-validated questionnaire and carried out dental examination at paediatric OPD. Results: Dental health problems were found in 364(42.8%) out of 850 subjects. Age was significantly associated (p<0.0001) with type of teeth involved. Incisors were most affected in infants and involvement of posterior teeth increased with age. Statistically significant (p<0.05) oral health risk factors were increasing age, lower socio-economic status, malnutrition, lower parents’ education, positive family history, bottle feeding, increased consumption of biscuits, fizzy drinks and chewing gum; delayed start and less time spent on brushing, infrequent change of toothbrush, incorrect brushing technique, inadequate parental knowledge and supervision. Conclusion: Dental screening can easily be incorporated in busy paediatric practice. An identification and record of individual risk factor is useful in selecting counselling strategies and monitoring.